Women on the Board and Managers’ Pay: Evidence from Spain - Lucas-Pérez, Maria Encarnación; Mínguez-Vera, Antonio; Baixauli-Soler, Juan Samuel; Martín-Ugedo, Juan Francisco; Sánchez-Marín, Gregorio (2015)
The current literature shows great interest in the issue of gender diversity on boards of directors. Some studies have hypothesized a direct relationship between diversity and the value of the firm, but not many examine the intermediate mechanisms that may exert an influence on such relationships. We employ two stages of GMM estimation methodology to exhibit evidences of the relationship between gender diversity and compensation of top managers in the Spanish context. Results show that gender diversity positively affects the effectiveness of boards—in terms of composition, structure, size and functioning—influencing a proper design of top managers compensation linked to company performance. Evidences suggest that legislative actions aimed at increasing the presence of women on boards of directors are justified not only for ethical reasons, but also for reasons of economic efficiency.
Keywords: Board characteristics; Top managers’ compensation; Governance effectiveness; Gender diversity; Board of directors